Rancang Bangun Sistem Informasi Inventory Obat di Puskesmas Cempaka OKU Timur Menggunakan Metode Fefo - Wahyu Paksi (Teknik Komputer Politeknik Negeri Sriwijaya, 2022)
Puskesmas is a functional implementing unit that acts as a center for health development, a center for fostering positions and residents in the health sector, as well as an early-level health service center that organizes activities in an equitable, integrated, and prolonged manner for residents who live in certain areas. But sometimes there are some cases found in the Puskesmas such as cases in the drug warehouse. This problem exists at the Cempaka Oku Timur Health Center. One solution to overcome this problem is to design and build an inventory data system for drug management in the warehouse. With the existence of a drug inventory data system, it is hoped that it can help drug management more easily. To achieve the goal in tackling this problem is to improve the drug supply data system with the Fefo method and use the Laravel framework using a mysql database. The results of the development show that the resulting drug inventory has features that can handle warehouse cases well and are useful for warehouse officers at the Cempaka Oku Timur Health Center.